Surface engineering of single-crystal NCM811 with graphene for enhanced mechanical integrity - Fasehullah, Muhammad; Jamil, Sidra; Ali, Ghulam; Chae, Keun Hwa; Jabar, Bushra; Mansoor, Adil; Tang, Chao (Elsevier BV, 2025)
The severity of cracking and planar gliding along (003) facets due to the irreversible phase transition and anisotropic volume change in single-crystalline Ni-rich layered oxides leads to sluggish redox kinetics and poor cycling performance. In this work, we coated the single-crystal LiNi0.8Co0.1Mn0.1O2 with exfoliated graphene nanoplates by using an amphiphilic surfactant oleic acid as an adhesive. The robust structure of graphene is uniformly coated on the surface, providing chemo-mechanical strength to the particle surface. The coating layer suppresses the irreversible phase transition and anisotropic volume change that effectively inhibits the mechanical stress and planar gliding during the long-term cycling. Additionally, the coating serves as a passivation layer that prevents the parasitic side reactions and mitigates the electrolytic infiltration into the particles, facilitating fast Li+ diffusion kinetics. Therefore, the modified cathode demonstrates a capacity retention of 92.2 % at 1C and 94.5 % at 5C between 2.7 and 4.3 V vs. Li+/Li compared to the pristine (70 % at 1C and 66.5 % at 5C). Hence, this coating strategy is beneficial to provide a shield against mechanical degradation and sluggish kinetics for single-crystal Ni-rich layered oxide cathodes.